1990
DOI: 10.1677/joe.0.1260043
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and insulin secretory studies on isolated porcine islets of Langerhans

Abstract: Since porcine islets are considered a likely tissue source for islet transplantation we have studied the insulin secretory responses to stimuli and some of the cell surface antigen characteristics of porcine islet cells. In a static incubation system, the threshold level of glucose required for the stimulation of insulin secretion from freshly isolated porcine islets was found to be between 2.8 and 4.2 mmol glucose/l. Arginine (5 mmol/l) and 3-isobutyl-l-methylxanthine (1 mmol/l) potentiated insulin release in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Despite these encouraging results, the in vitro physiology of porcine islets has not yet been examined in detail. Their in vitro insulin release after an acute glucose stimulus is weak (Marchetti et al 1989, Crowther et al 1990) when compared with the insuhn release from rat or human islets (Giannarelli et al 1993, Hegre et al 1993, Takei et al 1994 or to the insulin release induced in pig islets by glucose plus IBMX, a phosphodiesterase inhibitor (Heald et al 1992). In this study, porcine islets cultured overnight showed no insulin response to glucose, as already reported (Davalli et al 1993), and the insulin response was still low after 48-h culture in CMRL 1066.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these encouraging results, the in vitro physiology of porcine islets has not yet been examined in detail. Their in vitro insulin release after an acute glucose stimulus is weak (Marchetti et al 1989, Crowther et al 1990) when compared with the insuhn release from rat or human islets (Giannarelli et al 1993, Hegre et al 1993, Takei et al 1994 or to the insulin release induced in pig islets by glucose plus IBMX, a phosphodiesterase inhibitor (Heald et al 1992). In this study, porcine islets cultured overnight showed no insulin response to glucose, as already reported (Davalli et al 1993), and the insulin response was still low after 48-h culture in CMRL 1066.…”
Section: Discussionmentioning
confidence: 99%
“…However, isolated pig islets cultured in standard media show an extremely poor response to glucose; moreover, immunohistochem¬ istry data (Davalli et al 1993) and total islet glucagon content (Crowther et al 1989) in the whole pancreas and in the isolated islets have shown that peripheral -cells are usually lost during the isolation procedures employed for porcine islets. It is possible to speculate that the loss of -cells, induced by isolation, might be one of the reasons for these secretory abnormalities (Crowther et al 1990). In fact, -cells seem to be crucial in maintaining adequate cychc adenosine monophosphate (cAMP) levels within B-cells, required for a normal insuhn response to glucose (Schuit & Pipeleers 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, pigs would be suitable donors, since they have a digestive physiology, glucose homeostasis, and regulation of insulin secretion similar to that of humans. [89][90][91] Furthermore, the amino acid sequence of porcine insulin differs from human insulin by only one amino acid. 92 A major barrier to xeno-islet transplantation is hyperacute rejection, mediated by natural antibodies and cellular immunity.…”
Section: Alternative Sources Of Insulin-producing Tissuementioning
confidence: 99%
“…features with humans, including a structural similarity between porcine and human insulin (7). Transplantation…”
Section: Introductionmentioning
confidence: 99%